Development of a novel definitive scoring system for an enteral feed-only model of necrotizing enterocolitis in piglets - Ragan, Mecklin V.; Wala, Samantha J.; Sajankila, Nitin; Duff, Audrey F.; Wang, Yijie; Volpe, Samuel G.; Al-Hadidi, Ameer; Dumbauld, Zachary; Purayil, Nanditha; Wickham, Joseph; Conces, Miriam R.; Mihi, Belgacem; et al. (Frontiers in Pediatrics, 2023)
Introduction Necrotizing enterocolitis (NEC) is a complex inflammatory disorder of the human intestine that most often occurs in premature newborns. Animal models of NEC typically use mice or rats; however, pigs have emerged as a viable alternative given their similar size, intestinal development, and physiology compared to humans. While most piglet NEC models initially administer total parenteral nutrition prior to enteral feeds, here we describe an enteral-feed only piglet model of NEC that recapitulates the microbiome abnormalities present in neonates that develop NEC and introduce a novel multifactorial definitive NEC (D-NEC) scoring system to assess disease severity. Methods Premature piglets were delivered via Caesarean section. Piglets in the colostrum-fed group received bovine colostrum feeds only throughout the experiment. Piglets in the formula-fed group received colostrum for the first 24 h of life, followed by Neocate Junior to induce intestinal injury. The presence of at least 3 of the following 4 criteria were required to diagnose D-NEC: (1) gross injury score ≥4 of 6; (2) histologic injury score ≥3 of 5; (3) a newly developed clinical sickness score ≥5 of 8 within the last 12 h of life; and (4) bacterial translocation to ≥2 internal organs. Quantitative reverse transcription polymerase chain reaction was performed to confirm intestinal inflammation in the small intestine and colon. 16S rRNA sequencing was performed to evaluate the intestinal microbiome. Results Compared to the colostrum-fed group, the formula-fed group had lower survival, higher clinical sickness scores, and more severe gross and histologic intestinal injury. There was significantly increased bacterial translocation, D-NEC, and expression of IL-1α and IL-10 in the colon of formula-fed compared to colostrum-fed piglets. Intestinal microbiome analysis of piglets with D-NEC demonstrated lower microbial diversity and increased Gammaproteobacteria and Enterobacteriaceae. Conclusions We have developed a clinical sickness score and a new multifactorial D-NEC scoring system to accurately evaluate an enteral feed-only piglet model of NEC. Piglets with D-NEC had microbiome changes consistent with those seen in preterm infants with NEC. This model can be used to test future novel therapies to treat and prevent this devastating disease.